2020
DOI: 10.4274/tjps.galenos.2018.34392
|View full text |Cite
|
Sign up to set email alerts
|

Levocetirizine Dihydrochloride-Loaded Chitosan Nanoparticles: Formulation and <i>In Vitro</i> Evaluation

Abstract: Bu çalışmanın amacı, biyoyararlanımı iyileştirerek plazma ilaç konsantrasyonunu optimize etmek için uzatılmış etkiye ve yüksek yükleme kapasitesine sahip, mikron altı düzeyde levosetirizin dihidroklorür (LCD) yüklü kitosan nanopartijkülleri formüle etmektir. Gereç ve Yöntemler: Bu çalışmada LCD, oral uygulama amacı ile kitosan nanopartiküllerine püskürterek kurutma yöntemi kullanılarak yüklenmiştir. Nanopartiküllerin in vitro karakteristik özellikleri detaylıca incelenmiştir. Bulgular: LCD püskürterek kurutma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The spray drying process usually includes four stages: atomization, droplet mixing with dry gas, solvent volatilization, and product separation, in which the technological conditions and parameters of the atomization process play a decisive role in the droplet size distribution (Ré, 2006 ; Liu et al, 2015 ; Deshmukh et al, 2016 ; Messa et al, 2020 ), such as the selection of atomizer, nozzle pressure, feed or air flow rate, etc (Bowey & Neufeld, 2010 ; Shi et al, 2020 ). The spray drying method can generate particles in one step quickly and continuously, eliminating the need for a separate drying process in other preparation methods (Helbling et al, 2020 ; Ozturk & Kiyan, 2020 ; Yurtdas & Ozturk, 2020 ). The entire preparation process is automated, and a relatively high encapsulation rate can be obtained (Calegari et al, 2020 ), which is suitable for the encapsulation of proteins or peptides (Aydin, 2020 ; Shi et al, 2020 ), plasmid DNA (Walter et al, 2001 ; Atuah et al, 2003 ; Jilek et al, 2004 ), and small molecule drugs (Waldron et al, 2014 ).…”
Section: Preparation Methods Of Plga Microspherementioning
confidence: 99%
“…The spray drying process usually includes four stages: atomization, droplet mixing with dry gas, solvent volatilization, and product separation, in which the technological conditions and parameters of the atomization process play a decisive role in the droplet size distribution (Ré, 2006 ; Liu et al, 2015 ; Deshmukh et al, 2016 ; Messa et al, 2020 ), such as the selection of atomizer, nozzle pressure, feed or air flow rate, etc (Bowey & Neufeld, 2010 ; Shi et al, 2020 ). The spray drying method can generate particles in one step quickly and continuously, eliminating the need for a separate drying process in other preparation methods (Helbling et al, 2020 ; Ozturk & Kiyan, 2020 ; Yurtdas & Ozturk, 2020 ). The entire preparation process is automated, and a relatively high encapsulation rate can be obtained (Calegari et al, 2020 ), which is suitable for the encapsulation of proteins or peptides (Aydin, 2020 ; Shi et al, 2020 ), plasmid DNA (Walter et al, 2001 ; Atuah et al, 2003 ; Jilek et al, 2004 ), and small molecule drugs (Waldron et al, 2014 ).…”
Section: Preparation Methods Of Plga Microspherementioning
confidence: 99%
“…In the physical mixture, both the characteristic melting peaks of FA and the peaks belonging to the glass transition temperature of PLGA were observed. The disappearance of the FA melting peak in the A-FA coded NP formulation’s thermogram indicated that FA was diffused molecularly throughout the polymeric framework and contained in its amorphous state. , Furthermore, the thermogram demonstrated that FA and the polymers did not interact. These data obtained are important because the presence of the drug in molecular dispersion form helps with its extended-release feature …”
Section: Resultsmentioning
confidence: 99%
“…14 The positively charged amino groups of chitosan can bind to the negatively charged mucosal membranes, thus prolonging the time of contact. 15 As chitosan nanoparticles tend to have different properties compared to those of the bulk material, the former can be modified to suit the desired parameters. They can also be fashioned into nanospheres, nanocapsules, and nanofibers according to the need.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, since it is a linear polymer of glucosamine and acetylglucosamine, it biodegrades into harmless amino sugars that are absorbed by the body . The positively charged amino groups of chitosan can bind to the negatively charged mucosal membranes, thus prolonging the time of contact . As chitosan nanoparticles tend to have different properties compared to those of the bulk material, the former can be modified to suit the desired parameters.…”
Section: Introductionmentioning
confidence: 99%